Conditions and Needs for Positive Psychological Capital of Sports Students of Thailand National Sports University - Prommachan, Irisa; Janyam, Kanda (Thammasat Journal, 2026)
The purposes of this qualitative research were to study 1) the positive psychological capital situation of sports students at National Sports University, and 2) their needs for the promotion of positive psychological capital. Data were collected from documents on concepts, theories, and research related to positive psychological capital, as well as from field work. The researcher defined key informants and three target groups which were sports coaches, psychology lecturers, and sports students by purposive sampling. To collect data, the researcher interviewed representatives from each region using a semi-structured interview form that had been checked for content validity by experts. Data were analyzed using content analysis, and the findings were presented descriptively. The research results were as follows: The conditions of positive psychological capital of sports students at the National Sports University were in four dimensions. First, in terms of self-efficacy, students were well aware of their abilities in the role of athletes. However, they often lacked awareness of their learning roles. Second, optimism students trieds to show their strength or optimism, toward the situations they faced; on the other hand, they could sense a lack of understanding. Third, regarding hope, students often had short-term expectations or goals, lacked awareness of or planning for long-term goals in life. Fourth, with respect to resilience, students always learned and adapted to uncertain situations through sports competitions, leading to adaptation to the situations they faced. 2. Regarding the needs for positive psychological capital promotion of sports students at the National Sports University, it was found that sports students and those involved in caring for them needed or expected activities to enhance positive psychological capital through activity formats in each component of promotion and development in four dimensions. First, in terms of self-efficacy, activities could be designed for students to evaluate their own potential and abilities through learning from their own experiences and role models. Second, for optimism, activities could be designed to allow students to review themselves through past experiences; evaluate their perceptions of the stories that had happened. Third, regarding hope, example activities included having students consider their life goals and determine paths or methods that would lead to goals, creating motivation to achieve goals. Fourth, with respect to resilience, examples included counseling services, training, or activities that provided students with knowledge and understanding of being aware, accepting emotions, feelings, and adapting to unexpected situations. It was also desirable that student caregivers participate and learn about an important guideline for taking care of students in the future.